TINJAUAN YURIDIS PANCASILA SEBAGAI STAATFUNDAMENTALNORM DALAM MENGHADAPI KAPITALISME PENYELENGGARAAN PENDIDIKAN DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 12 TAHUN 2012 - Manurung, Ojak; Lubis, M. Yamin; Affan, Ibnu (Jurnal Ilmiah METADATA, 2021)
In practice, in the implementation of education in the field, the main idea is to get a large profit from the implementation of this education, especially in several non-government educational institutions. The formulation of the problem in this thesis is how to regulate the crime of money laundering, how to change the paradigm in the implementation of higher education in Indonesia after the issuance of Law Number 12 of 2012 concerning Higher Education, what is the form of the threat of capitalism currently facing the Indonesian nation in the administration of higher education what is the position of Pancasila as the fundamental norm in facing the threat of capitalism to the implementation of higher education in Indonesia. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results show that the paradigm shift in the implementation of higher education in Indonesia after the issuance of Law Number 12 of 2012 concerning Higher Education is seeking, discovering, disseminating, and upholding the truth. The form of the threat of capitalism currently faced by the Indonesian nation in the implementation of higher education is in the form of materialism, consumerism, hedonism, pragmatism, and instant attitudes that have become a serious threat to efforts to educate the nation's children to become superior human resources. All forms of barriers to education must be removed, including those caused by the inability to reach the cost of education. The position of Pancasila as a fundamental norm in facing the threat of capitalism to the implementation of higher education in Indonesia is that the strengthening of national identity, nationalism and culture is important for the education world to pay attention to in relation to the influence of globalization.